Influencia de la discapacidad en la dinámica de las familias del centro Senderos de Alegría. - Jiménez Maldonado, Sadia Paola. (2014)
Knowing that disability is a condition that modifies the development of the family as such, I have been important to the study "INFLUENCE OF DISABILITY IN FAMILY DYNAMICS OF THE CENTER SENDEROS DE ALGRIA", focused on intellectual disability; the same has been done in the middle of children and youth with special abilities "Senderos de Alegría", located in the area “La Paz”. It is descriptive, cross-sectional study during the period from September to November 2014 to determine how it influences the presence of a child with intellectual disabilities in the development of family dynamics, what kind of family it belongs, to know which element family dynamics is affected, and determine what were the most important socio-economic changes that have occurred in these families. The study group consisted of 82 parents who were mothers in their entirety, of children with special abilities Senderos de Alegría; and the sample of 28 mothers of children with intellectual disabilities who met the inclusion criteria. It was observed that children who come to the center "Senderos de Alegría", belong to a family structured, in 85.7% of the total; adaptability is also the most affected element family dynamic, leading mainly to chaotic families with a frequency of 75% of the families studied. In terms of socio-economic changes, the main change found in our study is the perception of discrimination against the child by the social environment, with 82.1% of the total population; and economic factors were also relevant, being so 78.6% of respondents reported that their economic spending had increased, mainly devoted to the pursuit of health professionals to care for your child / a with disability. Keywords: Influence, Intellectual Disability, Family Dynamics.